Ilencfalvi Szász Gerő (1831–1904) kéziratos hagyatékának feldolgozása - GERÉB, Miklós (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
Processing the Manuscripts of Szász Gerő of Ilencfalva (1831–1904) Szász Gerő was one of the most determining figures of the Transylvanian Reformed Church during the last quarter of the 19th century. He was dean in Kolozsvár, editor of the Prédikátori Tár (an omnibus volume of 35 Transylvanian preachers) and also editor of Erdélyi Protestáns Közlöny (the main, official newspaper of Transylvanian Reformed Church at that time.) Later he was elected vice bishop, and he stood very close to becoming even bishop of the church. His career, unfortunately, was broken when he lost the reliance of bishop Szász Domokos. He also wrote many poems, however, by publishing them, he never scored full marks from critics. We can admire his portrait also looking to the statue of King Matthew in Kolozsvár, since one of the king’s captains was modelled by Szász Gerő. We can find his manuscripts at the Central Archives of Transylvanian Reformed Church under mark „F2”. This short essay aims to introduce how many and what kind of sermons we can find between Szász Gerő’s manuscripts and to show the circumstances of their formation, and the author’s attitude to bible-passages has used.